Getting to know former students of PROFAE nursing courses - Bógus, Cláudia Maria; Bersusa, Ana Aparecida Sanches; Martins, Cleide Lavieri; Escuder, Maria Mercedes Loureiro (Revista da Escola de Enfermagem da USP, 2011)
The PROFAE (Professionalization Project in Nursing) was a relevant initiative for professional education. The objectives were to describe the profile of the former students of the technical nursing course of the São Paulo Health Department training centers so as to evaluate the effects of the course for the mobility and professional performance in the working market. Data collection was performed using a questionnaire answered by 216 former students and four focal groups with former students and nurse supervisors. Most respondents were women, with an average age of 42.2. The course received a positive evaluation, and two aspects were pointed out as motivating for searching for it: institutional support and COREN's resolutions. The former students perceive they had more initiative and theoretical preparation after the course. Nursing aide remains as the most common position in the area, thus causing dissatisfaction, because, especially in public services, technician positions are not available.